Orientação sexual nas escolas públicas no município de Bauru: as principais dúvidas dos jovens - Luciano, Karen Monique [UNESP]; Daré Neto, Luiz [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Deal about sexuality with young people in school isn’t an easy task, since the subject generates a lot of polemics and is not always taken seriously. The lack of resources in schools as well as trained professionals are limiting factors. In order to assist schools in the role of orientation of adolescents in preventing sexually transmitted diseases and unwanted pregnancies, lectures were made in various public schools in the city of Bauru and collected the main concerns of young people on the subject, with the help of an urn questions. Were accounted for 254 issues and divided into 5 categories: 29.13% were on anatomy/physiology, 18.9% of contraceptive methods and protection, 16.14% of pregnancy, 9.06% about STD, and 26.77% of the category others. Young people still treat it with little seriousness and from that, it is suggested that the topic be addressed more often and continuity for the family and school to build a safe and healthy sexuality.

Tratar sobre sexualidade com os jovens na escola não é uma tarefa fácil, visto que o assunto gera muita polêmica e nem sempre é levado a sério. A falta de recursos nas escolas, além de profissionais capacitados, são fatores limitantes. A fim de auxiliar as escolas no papel da orientação dos adolescentes na prevenção de doenças sexualmente transmissíveis e gravidez indesejada, foram feitas palestras em várias escolas públicas do município de Bauru e coletadas as principais dúvidas dos jovens acerca do tema, com o auxilio de uma urna de dúvidas. Foram contabilizadas 254 questões, sendo divididas em 5 categorias: 29,13% eram sobre anatomia/fisiologia, 18,9% sobre métodos contraceptivos e de proteção, 16,14% sobre gravidez, 9,06% sobre DST e 26,77% da categoria outros. Os jovens ainda tratam o assunto com pouca seriedade, e a partir disso, foi possível sugerir que o tema seja abordado com mais frequência e continuidade pela família e escola para construírem uma sexualidade segura e saudável.
Keywords: Sexual orientation; Questions about sexuality; Orientação sexual; Dúvidas sobre sexualidade